Absence of hypercoagulability after nCoV-19 vaccination: An observational pilot study. Issue 205 (September 2021) - Campello, Elena; Simion, Chiara; Bulato, Cristiana; Radu, Claudia M.; Gavasso, Sabrina; Sartorello, Francesca; Saggiorato, Graziella; Zerbinati, Patrizia; Fadin, Mariangela; Spiezia, Luca; Simioni, Paolo
Abstract: Background: It is still unknown whether COVID-19 vaccines induce a prothrombotic state or increase the hypercoagulable condition in subjects with a predisposition to thrombosis. Objectives: We evaluated the coagulation profile in a series of healthy subjects who received the first dose of the BNT162b2 or the ChAdOx1 vaccines and assessed whether hypercoagulability developed. Patients/methods: Volunteers among the staff of the University of Padua or health care professionals in the Padua University Hospital who had received either the ChAdOx1 or BNT162b2 vaccine in the previous 10 ± 2 days were eligible. A cohort of unvaccinated volunteers among family members of the University staff acted as control group. Global coagulation monitoring was assessed by whole blood rotational thromboelastometry, whole blood impedance aggregometry and thrombin generation. Platelet count was also obtained. Results: One hundred and ninety subjects were enrolled: 101 (53.2%) received the ChAdOx1 vaccine and 89 (46.8%) the BNT162b2 vaccine. Twenty-eight non-vaccinated subjects acted as controls. Thromboelastometry parameters were all comparable among groups. Thrombin receptor activating peptide (TRAP)-, ADP- and ASPI-induced platelet aggregation were similar among groups, as well as platelet count. Endogenous thrombin potential (ETP) was comparable among groups. The results were confirmed after controlling for age, gender and hormonal. Considering women taking combined oral contraceptives or thrombophilia carriers, no differences were detected in thromboelastometry or thrombin generation parameters between subjects who received ChAdOx1 vs. BNT162b2 vaccines. Conclusions: No significant activation of fibrinogen-driven coagulation, plasma thrombin generation or clinically meaningful platelet aggregation after ChAdOx1 or BNT162b2 vaccination was observed. Highlights: Global coagulation analysis of subjects who received BNT162b2 or ChAdOx1 vaccines Normal thromboelastometry profile after vaccination Normal platelet count and impedance aggregometry after vaccination Normal thrombin generation after vaccination No vaccine impact in coagulation for women taking contraceptives or thrombophilia carriers